ANALISIS KONSEPTUAL I'JAZ AL-QUR'AN SEBAGAI LANDASAN PENGUATAN PENDIDIKAN KEIMANAN ANAK - Ahmad Mukhlish Muhsin; Putri Aulia Citra Ritonga; Ummul Yakinah; Fawwas Fahlevi Yahya Nasution; Aulia Ramadhani (LPPM IAD Probolinggo, 2026)
This study examines I'jaz al-Qur'an as a foundation for strengthening the intellectual basis of Islamic faith. It aims to analyze the concept of the Qur'an's miracles through their definitions, essential conditions, and major dimensions. A qualitative library research method with a descriptive-analytical approach was employed by analyzing classical Ulumul Qur'an literature and contemporary scholarly sources. The findings indicate that i'jaz literally means rendering others incapable, highlighting human inability to imitate the Qur'an. A true mu'jizat must fulfill five essential conditions: it exceeds human capability, is extraordinary, confirms the truth of divine revelation, coincides with the Prophet's claim, and remains unmatched despite challenges (tahaddi). The study also identifies four principal dimensions of the Qur'an's miracles: linguistic excellence, scientific insights, news of the unseen, and scientific indications related to astronomy, geology, and embryology. By integrating classical scholarship with recent studies, including findings published in 2024, this research demonstrates the continuing relevance of I'jaz al-Qur'an in contemporary Islamic thought. The study contributes to Islamic education by providing a comprehensive framework for understanding the Qur'an's inimitability and its significance in reinforcing faith and rational inquiry in the modern era.